PENGARUH MODAL PSIKOLOGIKAL TERHADAP PERILAKU PELAYANAN YANG DIMEDIASI OLEH KETERIKATAN KERJA PADA PENGEMUDI OJEK ONLINE DI WILAYAH BANDA ACEH - Puan Az-Zahra; Lenny Rakhmawati (Jurnal Manajemen Inovasi, 2020)
This Study Aims To Measure The Influence Of Psychological Capital Influence On Service Behavior Mediated By Work Engagement To Ojek Online Drivers In The Banda Aceh Area. The Sample Used In This Study Was Ojek Online Drivers In The Banda Aceh Region, Totaling 135 Respondents. The Data Collection Equipment Used In This Study Is A Questionnaire. The Sampling Technique Used Was Convenience Sampling. Hierarchical Linear Modeling (Hlm) Is Used As An Analytical Method To Determine The Effect Of All The Variables Involved. Based On The Results Of Hlm Analysis, It Indicates That Psychological Capital Has A Positive Effect On Service Behavior, Psychological Capital Has A Positive Effect On Work Engagement, Work Engagement Has A Positive Effect On Service Behavior, And Work Engagement Mediates The Relationship Of Psychological Capital To Service Behavior.